A LEADERSHIP MODEL TO IMPROVE HIGHER SECONDARY MATHEMATICS TEACHERS’ TEACHING STRATEGIES AT DINDIGUL DISTRICT, SOUTH INDIA - Ye, Yan; Velankanni , Alex (Scholar: Human Sciences, 2022)
This study aimed to determine the leadership style to improve higher secondary mathematics teachers’ teaching strategies in Dindigul district, South India. The model was developed to enhance leadership style and teaching strategies. A qualitative method was used for the study. The leadership style a teacher possesses is one of the influential factors in students’ learning, inspiration, and output. Applying the type of suitable leadership style in their teaching is very important. There are many different types of leadership styles. However, the researcher explored leadership styles and teaching strategies for this study. Exploring the literature review, the researcher found that the secondary mathematics teachers in Dindigul District, South India used situational and transactional leadership styles. An interview was conducted with eight school leaders and found that the secondary mathematics teachers used three teaching strategies. The researcher developed a leadership model to improve higher secondary mathematics teachers’ teaching strategies from the leadership style and teacher’s teaching strategies. Hopefully, the higher secondary mathematics teachers, school leaders, and administrators will utilize the new leadership model.This study aimed to determine the leadership style to improve higher secondary mathematics teachers’ teaching strategies in Dindigul district, South India. The model was developed to enhance leadership style and teaching strategies. A qualitative method was used for the study. The leadership style a teacher possesses is one of the influential factors in students’ learning, inspiration, and output. Applying the type of suitable leadership style in their teaching is very important. There are many different types of leadership styles. However, the researcher explored leadership styles and teaching strategies for this study. Exploring the literature review, the researcher found that the secondary mathematics teachers in Dindigul District, South India used situational and transactional leadership styles. An interview was conducted with eight school leaders and found that the secondary mathematics teachers used three teaching strategies. The researcher developed a leadership model to improve higher secondary mathematics teachers’ teaching strategies from the leadership style and teacher’s teaching strategies. Hopefully, the higher secondary mathematics teachers, school leaders, and administrators will utilize the new leadership model.